Penyelesaian Perjanjian Kredit Terhadap Debitur yang Wanprestasi di Pt. Bank Perkreditan Rakyat Hari Depan Denpasar - Ni Made Lady Ruslya; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2021)
Indonesia is a developing country, this development is followed by rapid competition. In carrying out activities in any field, especially in economic activities, the community should not act recklessly but must follow the applicable norms. The government in an effort to equalize the welfare of its people creates a forum for community associations to process funds owned or borrowed funds to open a business. One of them is a bank that is engaged in the financial sector. People's credit banks are the government's solution to provide convenience to the community but with terms and conditions in the lending process. Every community who wants to borrow money for certain purposes can be done at BPR, those who want to borrow capital must have collateral which will later be calculated according to the desired loan, but it is not uncommon for bank staff to not think about the amount of collateral used with borrowed funds, resulting in frequent defaults. This study examines the factors that cause default in the credit agreement at PT. The People's Credit Bank for the Future of Denpasar and explained the efforts of PT. The People's Credit Bank of Denpasar is in the process of settling debtors who are in default. Researchers conduct direct information searches through interviews or empirical research with a case and legislation approach. Furthermore, the data were analyzed using qualitative descriptive. The factor for the occurrence of default is due to the negligence of the bank in complying with the rules that have been outlined. Efforts made to customers who are in default are conducting coaching, rescuduling, reconditioning and restructuring, if not fulfilled, a settlement will be carried out under the hands of selling both parties, the last stage is the determination of execution through the court. If the determination has been granted, the creditor immediately carries out the execution in accordance with.